2016
DOI: 10.1039/c5ra25862f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient oxygen electroreduction over ordered mesoporous Co–N-doped carbon derived from cobalt porphyrin

Abstract: High-performance self-supported Co–N-doped carbon electrocatalyst for ORR with comparable activity to Pt/C in both acidic and alkaline media was prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 60 publications
0
10
1
Order By: Relevance
“…2a ). The ORR current density at 0.8 V vs. a reversible hydrogen electrode (RHE) is 0.9 mA cm −2 for a loading of 800 µg cm −2 (12 µg Co cm −2 ), which compares well with state of art Co–N–C catalysts in acid medium, in spite of low cobalt content in Co 0.5 (refs 39 – 41 ). The Pt/C catalyst reaches 1.0 mA cm −2 at 0.91 V vs. RHE, and its higher activity is due to its higher atom-specific ORR activity (the higher Pt loading, 40 µg Pt cm −2 , resulting in identical number of metal atoms per cm 2 as for cobalt, due to the 3.3 times higher molar mass of Pt vs. Co).…”
Section: Resultsmentioning
confidence: 62%
“…2a ). The ORR current density at 0.8 V vs. a reversible hydrogen electrode (RHE) is 0.9 mA cm −2 for a loading of 800 µg cm −2 (12 µg Co cm −2 ), which compares well with state of art Co–N–C catalysts in acid medium, in spite of low cobalt content in Co 0.5 (refs 39 – 41 ). The Pt/C catalyst reaches 1.0 mA cm −2 at 0.91 V vs. RHE, and its higher activity is due to its higher atom-specific ORR activity (the higher Pt loading, 40 µg Pt cm −2 , resulting in identical number of metal atoms per cm 2 as for cobalt, due to the 3.3 times higher molar mass of Pt vs. Co).…”
Section: Resultsmentioning
confidence: 62%
“…Previous work have demonstrated that the presence of metal-N bond in the metal and nitrogen coexisting system is responsible for the high catalytic activity for the ORR. 54,55 In the work presented here, however, the metal-N bonds are not detected in both the XPS spectra of Co 2p and N 1s, which clearly rules out the presence of the metal-N bond in the Co-CoO@NC/NC-800 and its contribution to the higher catalytic activity of the Co-CoO@NC/NC-800. On the basis of this and the results shown above, we therefore attribute the following aspects to the main reasons responsible for the high catalytic activity of the Co-CoO@NC/NC-800: (1) strong electronic interaction between the Co-CoO nanoparticles and the NC, (2) high specic surface area of the Co-CoO@NC/NC-800, (3) small and uniformly sized Co-CoO nanoparticles, (4) good electric conductivity of the Co-CoO@NC/NC-800 due to its well carbonized structure, (5) good hydrophilicity of the Co-CoO@NC/NC-800 due to the presence of the NC.…”
Section: Electrochemical Measurementcontrasting
confidence: 53%
“…Another important factor regarding to the application as electrocatalyst electrode material is number of electrons transfer during the ORR process 15 . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For alkaline ORR measurements, loading amount of Pt/C (20%) was ~0.1 mg.cm −2 , which contain loaded Pt quantity of ~20 μg cm −2 . Koutecky-Levich (K-L) relation was used to calculate the kinetic Parameters 15,16 . The mechanism of the mesoporous Fe-doped C12A7:e − composite will be discussed in detail to practically demonstrate that the Fe-doped C12A7:e − composite can exhibit higher electrocatalytic activity towards ORR in the fuel cell.…”
Section: Fe-doped C12a7:e− Composite Synthesismentioning
confidence: 99%